The interaction of some halogenated anaesthetic agents with hepatic drug metabolizing enzymes - Marsh, Julia Anne (University of Cape Town, 2016)
Bibliography: pages 183-200. === This thesis comprises a report of investigations into the interaction of the volatile anaesthetic agents, fluroxene, 2,2,2-trifluoroethyl ethyl ether(TFEE), methoxyflurane and enflurane, with hepatic drug metabolizing enzymes in vivo and in vitro. Each of the anaesthetic agents interacts with the type P-450 cytochromes of hepatic microsomes in vitro resulting in the appearance of a type I difference spectrum, enhancement of NADPH oxidation and production of potentially toxic metabolites, 2,2,2-trifluoroethanol (TFE) (from fluroxene and TFEE) and free fluoride ion (from methoxyflurane and enflurane).